Early Cenozoic exhumation in the Qilian Shan, northeastern margin of the Tibetan Plateau: Insights from detrital apatite fission track thermochronology. (16th June 2020) - He, Pengju; Song, Chunhui; Wang, Yadong; Meng, Qingquan; Wang, Daichun; Feng, Ying; Chen, Lihao; Feng, Wei
Abstract: The Qilian Shan is a reactivated fold‐thrust belt at the northeastern margin of the Tibetan Plateau (TP). The initiated timing of the Qilian Shan's tectonic response to Indian‐Asian plate convergence has significant implications for our understanding of the growth of the TP, yet remains a controversial topic. We conducted apatite fission track analyses of the Cenozoic synorogenic sediments in the Subei Basin on the northwestern flank of the Qilian Shan to investigate the time of initial Qilian Shan deformation during the Cenozoic. An integration of new and existing detrital apatite fission track ages indicates that terranes in the Qilian Shan experienced a prominent tectonic exhumation event at 60–50 Ma. This result suggests that tectonism initiated on the northeastern margin of the TP nearly simultaneously with the India‐Asia collision.